2010
DOI: 10.1142/s0218810410004837
|View full text |Cite
|
Sign up to set email alerts
|

Slac Wrist in the Absence of Recognised Trauma and CPPD

Abstract: This study suggests that non-traumatic SLAC does exist. We believe that non-traumatic SLAC begins with abnormal wrist kinematics and that the dorsal radiolunate ligament restricts lunate flexion but not scaphoid flexion, leading to increased SL angles and, with years, eventual attrition of the SL ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This is similar to the results of previous studies investigating post-arthroscopic chondrolysis of the shoulder (24,25). SLAC tends to be seen in older patients (26). The mean time of disease onset (development interval of demonstrable joint space narrowing after arthroscopy) was 1.63 years in patients with PRCC.…”
Section: Progression Of Prccsupporting
confidence: 89%
“…This is similar to the results of previous studies investigating post-arthroscopic chondrolysis of the shoulder (24,25). SLAC tends to be seen in older patients (26). The mean time of disease onset (development interval of demonstrable joint space narrowing after arthroscopy) was 1.63 years in patients with PRCC.…”
Section: Progression Of Prccsupporting
confidence: 89%
“…Those causes are more commonly observed in patients with bilateral wrist changes. 28,[34][35][36] analyzed radiographs from both wrists of 1,000 people with no recent trauma, and found 67 of those cases of bilateral and 51 of unilateral SL space widening. 34 There were signs of SLAC in 26 wrists, and, of those, 9 were bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…SLAC is the most common pattern of osteoarthritis in the wrist (Watson and Ryu, 1986). The most frequent aetiology is believed to be a traumatic injury of the scapholunate ligament (Kitay and Wolfe, 2012), but cases of nontraumatic SLAC wrists have been reported (Pollock et al., 2010). Masmejaen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Masmejaen et al. (1997) reported that bilateral SLAC wrists were extremely rare, but Pollock et al., (2010) found 11 bilateral cases out of 17 patients with SLAC wrists. Bilateral cases of SLAC wrist have also been observed in patients with calcium pyrophosphate crystal deposition disease (Chen et al., 1990).…”
Section: Discussionmentioning
confidence: 99%